THOSE BORING, ARCANE PART-WRITING EXERCISES - L. Poundie Burstein (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2020)
Music theory students and teachers alike have long complained about the sterile part-writing exercises that are a staple of music theory classes. With glee people love to point out how works from the repertoire frequently feature elements that are forbidden in exercises, thereby seeming to prove the ineptitude of the arcane rules forced upon generations of students. Considering the glaring divide between compositional practice and the guidelines for these exercises, are there truly any benefits for continuing to teach in this old-fashioned manner? If their purpose is to mimic a specific artistic style, such as witnessed in the chorales of J. S. Bach, then the utility of part-writing exercises would indeed be extremely questionable. But if their goals are more properly understood as a means of enhancing sensitivity to certain basic procedures of tonal music, then part-writing exercises could rightly be valued as important pedagogical tools for developing vital skills that in turn can inform the performance, hearing, analysis, and composition of tonal music.
Keywords: music theory pedagogy; part-writing; harmony; exercises